THE URGENCY OF STRATEGIC MANAGEMENT IN HIGHER EDUCATION : A SYS TEM ATIC LI T ERA TU RE R EVI E W APPROACH - M. Alang Khairun Nizar (PT. Radja Intercontinental Publishing, 2026)
Universities are institutions of higher learning that play a strategic role in nation building. Developed countries generally have high-quality higher education systems capable of producing superior human resources, innovative research, and significant contributions to economic, social, political, and cultural development. Conversely, the poor quality of higher education often results in a nation's low competitiveness on the global stage . This article aims to explain the Strategic Management of Higher Education from an Islamic perspective. The method used in this article is qualitative research with a Systematic Literature Review approach. Articles were collected from Google Scholar using the PRISMA ( Preferred ) search process . R e p or t ing I t e m f o r Sy s t e m ic R e vi e wsand​ M e ta- a n a ly ses ) . Then​​​​ done​​​​​​​ analysis​​​​​​ is i s e c a ra de s k r i p t i f. The results found that strategic management is based on the strategy formulation stage, the formulation of the decided strategy must be calculated in order to provide the greatest benefit for the company, with activities ranging from developing a business mission, understanding external opportunities and threats, determining internal strengths and weaknesses and establishing long-term objective plans. Strategy implementation, is formulating to change the established strategy into a management action. Activities at this stage include annual objective policies, allocating resources and mobilizing organizational actors. Strategy evaluation, is the final stage of strategic management with its main activities being to review the internal and external factors that form the basis of the current strategy, measuring performance and taking corrective action.